2012
DOI: 10.21608/ajfm.2012.19480
|View full text |Cite
|
Sign up to set email alerts
|

Study of Electrocardiographic Changes Associated with Acute Poisoning in Tanta Poison Center

Abstract: Poisoning or intoxication is the occurrence of harmful effects resulting from exposure to a foreign substance. According to the Center for Disease Control, approximately 1 million of the 110 million annual emergency department (ED) visits are related to poisoning and other toxic effects. Electrocardiogram (ECG) is a noninvasive, relatively inexpensive diagnostic test that provides important information regarding not only the heart, but also non-cardiac events impacting the cardiac system. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(39 reference statements)
3
1
0
Order By: Relevance
“…This partially came with poisoning severity score used by El Masry and Tawfik (2013) in 2011 annual report of Ain Shams poison control center who classified poisoned patients to low severity (75.1%), moderate (20.7%) and high severity (4.2%). Also, partially in agree with Heshmat et al, (2012) in Tanta study of ECG changes in acute poisoning who also classified GCS low (≤8) in (12.7%) of 282 studied patients, moderate (12-9) in (42.6%), while was high (≥13) in (44.7%) of patients. GCS less than eight had been more associated with mortality in children presenting with poisoning also, GCS of 8 or less were more liable to be intubated (Eizadi Mood et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…This partially came with poisoning severity score used by El Masry and Tawfik (2013) in 2011 annual report of Ain Shams poison control center who classified poisoned patients to low severity (75.1%), moderate (20.7%) and high severity (4.2%). Also, partially in agree with Heshmat et al, (2012) in Tanta study of ECG changes in acute poisoning who also classified GCS low (≤8) in (12.7%) of 282 studied patients, moderate (12-9) in (42.6%), while was high (≥13) in (44.7%) of patients. GCS less than eight had been more associated with mortality in children presenting with poisoning also, GCS of 8 or less were more liable to be intubated (Eizadi Mood et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…The collected data revealed that ECG readings during the first 24 of admission of the studied patients were normal in (44%), (28%) had sinus tachycardia, (9%) had sinus bradycardia, (4%) for each prolonged QTc and inverted T, (3%) had ST elevation, (2%) for each heart block, AF and PVCs and (1%) for each sinus arrest and SVT. These results partially coincided with the study conducted on 282 cases of acute poisoning admitted to Tanta Poison Center during the period from the start of July -2009 to the end of June -2010 by Heshmat et al [3] to evaluate the ECG changes they found that 58.51% of patients had ECG changes. These were: sinus tachycardia followed by prolonged QTc interval then sinus bradycardia and lastly nodal tachycardia.…”
Section: Bar Graph Illustrates Independent T Test Statistical Analysupporting
confidence: 88%
“…In the current study 94% survived and 6% of patients died.Varieties of toxins were involved in the study as pesticides and hydrocarbons, therapeutic drugs as (CVS drug, CNS drugs and theophylline), drugs of abuse, bites and PPD. CNS drugs occupied the highest percentages among studied patients 25% then cardiovascular drugs and pesticides each have 15%, while, CO poisoning in the last just have 1% this agree with Tanta study of ECG changes by Heshmat et al [3] who found that major toxic agents were therapeutic drugs and pesticides. Also, the cardiovascular drugs showed that BBs (6%), digitalis (5%) and CCBs (4%) this agree with Hussein (et al (2018) who showed that beta blockers toxicity was the commonest cardiovascular drug toxicity followed by digitalis and finally calcium channel blockers.…”
Section: Bar Graph Illustrates Independent T Test Statistical Analysupporting
confidence: 84%
See 1 more Smart Citation